2017
DOI: 10.1038/ncomms15596
|View full text |Cite
|
Sign up to set email alerts
|

End-Triassic mass extinction started by intrusive CAMP activity

Abstract: The end-Triassic extinction is one of the Phanerozoic's largest mass extinctions. This extinction is typically attributed to climate change associated with degassing of basalt flows from the central Atlantic magmatic province (CAMP). However, recent work suggests that the earliest known CAMP basalts occur above the extinction horizon and that climatic and biotic changes began before the earliest known CAMP eruptions. Here we present new high-precision U-Pb ages from CAMP mafic intrusive units, showing that mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
229
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(251 citation statements)
references
References 65 publications
16
229
0
6
Order By: Relevance
“…In fact, a single short-lived CAMP magmatic pulse (ca. 10 5 km 3 erupted over 0.5 kyrs) [21][22][23] may emit about 5 × 10 16 mol CO 2 , roughly the same total amount of projected anthropogenic emissions over the 21st century, according to the Representative Concentration Pathway 4.5 57 . This scenario for rapid CO 2 emissions predicts a global temperature increase of about 2°C and an oceanic pH decrease of about 0.15 units over 0.1 kyrs, and Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, a single short-lived CAMP magmatic pulse (ca. 10 5 km 3 erupted over 0.5 kyrs) [21][22][23] may emit about 5 × 10 16 mol CO 2 , roughly the same total amount of projected anthropogenic emissions over the 21st century, according to the Representative Concentration Pathway 4.5 57 . This scenario for rapid CO 2 emissions predicts a global temperature increase of about 2°C and an oceanic pH decrease of about 0.15 units over 0.1 kyrs, and Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We examine the implications of these findings for magma eruption history and subsequent impact on the global climate. The emplacement of CAMP (peak activity at 201.6-201.1 Ma) occurred during the early stages of the Pangaea supercontinent break-up, leading to the opening of the Central Atlantic Ocean, and is synchronous with the End-Triassic Extinction (ETE), one of the five most severe biotic crises during the Phanerozoic [19][20][21][22] . At least 3 × 10 6 km 3 of CAMP basaltic magmas were erupted or intruded into the continental crust over an area of 10 7 km 2 in brief pulses, from a few centuries to a few millennia each, characterized by high eruption rates 6,23 .…”
mentioning
confidence: 99%
“…Igneous zircon is not everywhere present in gabbro, although co-existing baddeleyite and zircon occurs, especially in coarse-grained rocks where the two minerals are interpreted as formed during a late magmatic stage from a Zr-saturated melt (Heaman & LeCheminant, 1993;Scoates & Chamberlain, 1995), and a shift in Si-activity (Butterman & Foster, 1967). Studies have shown that igneous zircon and baddeleyite can co-crystallize (Allibon et al, 2011;Beckman et al, 2014;Davies et al, 2017;Wingate, 2001). Texturally we have noticed that when igneous zircon and baddeleyite are next to one another, baddeleyite may be rimmed by small grains of igneous zircon that have more well-developed crystal faces than typical metamorphic polycrystalline zircon.…”
Section: Igneous Zircon and Baddeleyitementioning
confidence: 99%
“…Az éghajlatmódosító gázok nem csak közvetlenül eredtek a KAMP kigázoso -dásából és a felszínre került kőzetek mállásából. Emellett a tengeraljzati üledékben csapdázódott metán-hidrátnak a fo kozatos felmelegedéstől beinduló disszociációjából (BEERLING & BERNER 2002), illetve a szervesanyag-tartal mú üledékes kőzetekbe nyomuló szubvulkáni intrúziók révén képződő termogén metánból (DAVIES et al 2017), illetve ezek légköri oxidációjakor keletkező szén-dioxidból vezethető le a szuper üvegház-felmelegedés szcenáriója. En nek legmarkán sabb geokémiai bizonyítékai a negatív szén izotóp-anomáliák.…”
Section: A Triász Végi Kihalás éS a Környezeti Változások Lehetségesunclassified